Analysis Of Future Health Insurance Premium Reserve Calculations Using The Commissioners Method With Woolhouse Formula - oktavia handayani; hendra cipta (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
A premium reserve is the amount of funds that the insurance company needs to prepare for the payment of liability benefits when a claim occurs. One method of calculating premiums is the commissioners method which is an extension of the prospective reserve method.The main factor in the actuarial calculation is the mortality rate that can be determined using the WOOLHOUSE mortality law. This study aims to determine the size of the life insurance premiums reserve using the commisioners method and the WOLHOUSE mortality laws. The calculation of the premium reserve is linked to the determination of a person's chances of survival over a period of years of WOALHOUSE law which is then used to find the value of the insurance, the initial annuity value, the annual premium, the modified premiums based on the Commissioners method, and the amount of the premie reserve at the end of the year. The study was conducted on a 25-year-old woman who was enrolled in a dwiguna life insurance program with a 25 year liability period and a 23 year premium payment period at a 4% interest rate with a liability of Rs. 500,000,000. The results of the analysis showed that the large reserves of premiums obtained at the end of the period of liability with the Commissioners method and the WOOLHOUSE mortality law are equal to the given reservation value, so that the insurance company is prepared to give the amount of reservation promised to the policyholder.